2014
DOI: 10.4103/2230-8210.137499
|View full text |Cite
|
Sign up to set email alerts
|

Completion report : Effect of Comprehensive Yogic Breathing program on type 2 diabetes: A randomized control trial

Abstract: Background:Yoga has been shown to be beneficial in diabetes in many studies, though randomized control trials are few. The aim of this randomized control trial was to see the effect of Sudarshan Kriya and related practices (comprehensive yogic breathing program) on quality of life, glycemic control, and cardiac autonomic functions in diabetes. Diabetes mellitus is a risk factor for sudden cardiac death. Cardiac autonomic neuropathy has been implicated in the causation of sudden cardiac death. Therefore, a mane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 5 publications
(6 reference statements)
2
25
1
Order By: Relevance
“…In most studies (20/23, 87%) participants with medical complications (e.g., coronary artery disease, renal disease) were excluded. Only two studies used HbA1c levels as inclusion criteria: Beena and Sreekumaran (2013) included participants with HbA1c > 8% and Jyotsna et al (2014) included participants with HbA1c between 6 and 9%. The mean retention rate was 92% (SD = 0.13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies (20/23, 87%) participants with medical complications (e.g., coronary artery disease, renal disease) were excluded. Only two studies used HbA1c levels as inclusion criteria: Beena and Sreekumaran (2013) included participants with HbA1c > 8% and Jyotsna et al (2014) included participants with HbA1c between 6 and 9%. The mean retention rate was 92% (SD = 0.13).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies (6/23, 26%) identified the style of yoga used in the intervention. Of the six studies reporting the style of yoga intervention, three used hatha yoga (Gordon et al, 2008b; Pardasany et al, 2010; Sri et al, 2014) and three used Sudarshan-kriya yoga (Agte and Tarwadi, 2004; Balaji and Thirumaran, 2015; Jyotsna et al, 2014). The sampled studies reported using several yoga components (not mutually exclusive) including postures (22/23, 96%), breathing exercises (21/23, 91%), relaxation techniques (16/23, 70%), meditation (9/23, 39%), and yogic philosophy (2/23, 9%).…”
Section: Resultsmentioning
confidence: 99%
“…The total sample size ranged from 20 to 277. A total of 11 RCTs were carried out in four countries, including the UK, India, Cuba and Iran. Two RCTs were carried out by Gordon et al .…”
Section: Resultsmentioning
confidence: 99%
“…The goals of yoga, a Sanskrit term meaning "yoke or union," do not center primarily on physical fitness, but rather on integration of mind, body, and spirit, cultivation of balance, calm, harmony, and awareness, and, in classic yoga traditions, the attainment of selflessness and spiritual enlightenment. 8,9 Of the several major branches of yoga, the most widely practiced forms include Raja (royal or classical) yoga and the closely related Hatha yoga, sometimes known as the yoga of activity. 8,9 A growing body of evidence suggests yoga practice may reduce risk for CVD and lead to improvements in physical health and well-being in a range of populations, potentially including those with DM2.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Of the several major branches of yoga, the most widely practiced forms include Raja (royal or classical) yoga and the closely related Hatha yoga, sometimes known as the yoga of activity. 8,9 A growing body of evidence suggests yoga practice may reduce risk for CVD and lead to improvements in physical health and well-being in a range of populations, potentially including those with DM2. 10 The present study endeavours to outline the effects of practice of Raja yoga meditation in obtaining glycaemic control and correcting dyslipidemia in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%